American tacos : a history and guide - Ralat, José R. (University of Texas Press, 2020)
"Not all tacos are Mexican, but that doesn't mean they aren't authentic--or delicious. José Ralat has written a survey of American tacos--that is, tacos that developed on this side of the border. Some, like the breakfast taco, barbacoa, the puffy taco, or the Korean-flavored "KMex" taco, are relatively familiar, while others such as the fry bread taco or kosher taco belong to a distinctive culture that is not as well known. Ralat examines the roots and history of these tacos through archival research and interviews with the taqueros, taco lovers, and families of those who make them today. In the process, many of the best purveyors of each variety are identified, making the book a useful guide for anyone interested in a taco road trip across America. No recipes are included, but in addition to the chapters devoted to various taco styles, there are short pieces on "five signs of a truly outstanding taco joint," "a brief history of the taco holder," and a guide to taco festivals around the country. Photos are available for each chapter. Notes on sources round out the book"--